The Effect of Problem Based Learning Work Sheet Usage on Student Learning Outcomes - Diah Astuti, Enny; Susanto, Rachmat; Cahyono, Didik; Sudirman , Sudirman; Tri Astuti , Missi (Mudir : Jurnal Manajemen Pendidikan, 2023)
The purpose of this study is to ascertain how students' learning outcomes for the idea of harmonic vibrations are affected by the use of problem-based learning-based student worksheets. One of high schools served as the research site. A quasi-experiment with a non-equivalent control group design was the study methodology employed. Purposive sampling was the method of sampling that was utilized. Multiple choice questions are employed as part of the test instrument. Two classes that the school permitted to be researched and that were split into experimental and control classes served as the study's samples. The results of hypothesis testing using the t-test show that the application of problem-based learning-based student worksheets on student learning outcomes on the concept of harmonic vibrations produces significant results with a significant value less than the significance level. That is, the use of problem-based learning student worksheets has an influence on student learning outcomes for the idea of harmonic vibrations.